Positive and nodal solutions for nonlinear nonhomogeneous parametric Neumann problems - Nikolaos S. Papageorgiou; Calogero Vetro; Francesca Vetro (Electronic Journal of Differential Equations, 2020)
We consider a parametric Neumann problem driven by a nonlinear nonhomogeneous differential operator plus an indefinite potential term. The reaction term is superlinear but does not satisfy the Ambrosetti-Rabinowitz condition. First we prove a bifurcation-type result describing in a precise way the dependence of the set of positive solutions on the parameter $λ>0$. We also show the existence of a smallest positive solution. Similar results hold for the negative solutions and in this case we have a biggest negative solution. Finally using the extremal constant sign solutions we produce a smooth nodal solution.